The Effect of Couple's Motivational Interviewing on Exposure to Secondhand Smoke Among Pregnant Women at Home - Roghieh Bayrami; Samira Ebrahimi; Javad Rasouli; Haydeh Feizipour (Journal of Family and Reproductive Health, 2022)
Objective: Secondhand smoke (SHS) during pregnancy is associated with many maternal-fetal complications. Iran has a high male smoking prevalence rate. This study aimed to determine the effect of motivational interviewing with couples on exposure to SHS at home in pregnant women referring to health centers in Urmia in 2019. Materials and methods: A randomized control trial was performed on 112 non-smoking pregnant women with smoking husbands, randomly allocated into two groups (each with 56 members). The participants were asked to specify the daily average times and duration of exposure during the last week. Five motivational interviewing sessions were held for the members of the intervention group. Each session lasted90 minutes and two sessions were held per week.  The data were collected before and four weeks after the intervention. The data were analyzed using the repeated-measures analysis of variance (ANOVA) by SPSS-20 at a significance level of 0.05. Results: Of 112 couples who were randomized, 102 (91.07%) completed the trial. There was a significant reduction in terms of the daily frequency and duration of SHS exposure of the husband one week and one month after the intervention in the intervention group. The daily frequency and duration of SHS exposure of people other than the spouse at home did not decrease over time. Conclusion: Following the results of the study, the couple-based motivational interviewing approach can be used to reduce SHS exposure in women at home.